Shakespeare's Feet: Puns, Metre, Meaning. Issue 3 (March 2015) - Stagg, Robert
Abstract This essay attempts to explain one of Shakespeare's strangest stage directions, at the end of Coriolanus. To do so, it looks at one of Shakespeare's most‐used puns: the way a 'foot' can be an anatomical foot or a prosodic foot. In Shakespeare's writing, this punning relationship between anatomical and prosodic feet speeds or slows verse, characterises personages like Iago, and even rescues poetry from the ravages of time. The reason, it transpires, this pun works so well in Shakespeare's writing is that it speaks to the ways in which metre operates in a manner akin to pun: prising multiple interpretations from words in order to prize them.